Fighting stigma with Self-Image: The resistance strategy of the pegayaman muslim community in Bali - Kumbara, A. A. Ngurah Anom (ETNOSIA : Jurnal Etnografi Indonesia, 2022)
The stigmatization of the Pegayaman Muslim community has resulted in various forms of violence, both physical and symbolic. The aim of this study is, therefore, to examine how the Pegayaman Muslim community fights stigma by building a positive self-image in the structure of a pluralistic society in Buleleng, Bali. Furthermore, the data used in this study was collected through observation, in-depth interviews, and documentation studies by increasing the number of researchers on the field and analyzed using a three-phase interpretive-critical approach, namely data reduction, data presentation, and verification. The results revealed that the Pegayaman Muslim community faced stigmatization as a result of historical experiences; religious and ethnic ideological discourses; and the construction of reality for various interests. There were different forms of stigma ranging from labeling to discrimination in various social practices. The community responded to this stigma by building a positive self-image. Also, the inhabitants sought to improve their quality of life through economic empowerment, educational awareness, the establishment of Islamic values, building an image as an inclusive and tolerant Islamic community, creating a cohesive space for communication and interaction with the surrounding peoples, and optimizing the role of the media. In this situation, it was found that self-image is an effective strategy that can be used in curbing the inherent stigmawhile increasing the dignity of the inhabitants of a multicultural society.